2011
DOI: 10.1038/ncomms1277
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic vortex core reversal by excitation of spin waves

Abstract: Micron-sized magnetic platelets in the flux-closed vortex state are characterized by an in-plane curling magnetization and a nanometer-sized perpendicularly magnetized vortex core. Having the simplest non-trivial configuration, these objects are of general interest to micromagnetics and may offer new routes for spintronics applications. Essential progress in the understanding of nonlinear vortex dynamics was achieved when low-field core toggling by excitation of the gyrotropic eigenmode at sub-GHz frequencies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
201
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 219 publications
(214 citation statements)
references
References 45 publications
10
201
1
2
Order By: Relevance
“…It has been demonstrated that the vortex core polarity can be dynamically reversed by exciting one of the eigenmodes of the vortex structure, i.e., the gyrotropic mode [1][2][3][4] or dipolar spin-wave modes. [5][6][7] For the vortex gyrotropic mode G 0 , the vortex core performs a translational motion with frequencies in the range of 100 MHz to 1 GHz (depending on the disk dimensions and the material of the disk). 8 Dipolar spin-wave modes have frequencies in the GHz range and describe dynamic excitations of the planar part of the vortex structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the vortex core polarity can be dynamically reversed by exciting one of the eigenmodes of the vortex structure, i.e., the gyrotropic mode [1][2][3][4] or dipolar spin-wave modes. [5][6][7] For the vortex gyrotropic mode G 0 , the vortex core performs a translational motion with frequencies in the range of 100 MHz to 1 GHz (depending on the disk dimensions and the material of the disk). 8 Dipolar spin-wave modes have frequencies in the GHz range and describe dynamic excitations of the planar part of the vortex structure.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of focused X-rays has spread continuously over recent decades and includes applications such as imaging, chemical analysis (Sakdinawat & Attwood, 2010) and time-resolved investigation by exploiting pulses of synchrotron radiation (Kammerer et al, 2011;Van Waeyenberge et al, 2006;Saes et al, 2003). In contrast to electron microscopy, X-ray microscopy provides high penetration depth and enables three-dimensional imaging of complete cells (Vogt et al, 2000), large alive biological samples (Olendrowitz et al, 2012) and in situ investigation under extreme conditions (Fife et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the excitation of spin wave modes from out-of-plane magnetization components from the central vortex. 17 The spin waves confine at higher field frequencies up to 4 GHz (Fig. 10(g) and 10(h)).…”
Section: Magnetization Precession and Spin Waves -Ghz Dynamicsmentioning
confidence: 99%
“…The spin waves can be excited by different means, for instance not only by using microwave antennas, 14 but also from domain wall oscillations 15,16 and magnetic vortex reversal. 17 Here, we present a proof of the generation of spin waves from flux-closed vortex configuration via time-resolved MOKE imaging. Fig.…”
Section: Magnetization Precession and Spin Waves -Ghz Dynamicsmentioning
confidence: 99%